Design of Planetary Gear Transmission Mechanism for Electric Actuator - Jianjun Nie; Yingjie Yu; Hongzhen Yan (Jixie chuandong)
In order to meet the needs of industrial automation places with narrow installation space， a compact electric actuator is developed by taking NGWN （II） type （3Z） planetary gear mechanism as the main transmission mechanism and combining the fixed axis gear train and worm gear drive. In order to shorten the design cycle and reduce the workload of manual calculation，a multi-objective optimization mathematical model of planetary gear mechanism is established and solved with the volume and efficiency as design objectives， and the design parameters of electric actuator are obtained. On this basis， the three-dimensional model of the electric actuator is established， and finally the manufacturing of the electric actuator is completed. The results show that， for the NGWN （II） type （3Z） planetary gear mechanism with small modulus， when the average value of the reference center distance of all gear pairs or that of two of the gear pairs is taken as the common actual center distance， the calculated profile shift coefficient of each involute gear is more reasonable， and the design result is more in line with the actual requirements.